Determining and Estimating the Creep of Tigris Riverbanks at the Baghdad University Camp Using GIS Analytical Symmetrical Difference Method - S. Mahdi, Ala; Mustafa Ali, Mahdi (Iraqi Journal of Science, 2021)
The Tigris River in Iraq is of highly meandering in several of its parts. So, the largest meandering inside Baghdad City, is in Al-Jadriyah. During its course, the Tigris Riverbanks are facing erosion frequently due to alteration in the geomorphological and hydrological characteristics affecting the river channel. The entire length of Tigris River from the northern entrance of Baghdad to the convergence with Diyala River at southern of Baghdad is about 49 km length. The Tigris River is suffering from the erosion, deposition, and migration conditions. The river migration was found as maximum in the left bank at the side of the University, and lesser in the right bank in the opposite side, Dora. The aim of this study is to measure the magnitude of changes happened to the Tigris Riverbanks adjacent to the Baghdad University Camp in Al-Jadriyah for a period of last fifty years extended between 1962 and 2013, using Remote Sensing (RS) and Geographic Information System (GIS) techniques. Symmetrical Difference Analytical method was used to obtain changes for Tigris Riverbanks in the study area. The obtained results in this study demonstrate that Remote Sensing and Aerial Photography are important sources of data in monitoring and detecting the movement of Tigris riverbanks. Accordingly, the measured areas of deposition and erosion are (657 073 m2) and (173 087 m2) respectively, and the ratio between them was 3.83 to 1.